Polarimetric diversity in tidal disruption events: Comparative study of low-polarised sources with AT2020mot - Floris, Alberto; Liodakis, Ioannis; Koljonen, Karri I. I.; Lindfors, Elina; Agis-Gonzalez, Beatriz; Paggi, Alessandro; Blinov, Dmitry; Nilsson, Kari; Agudo, Iván; Charalampopoulos, Panagiotis; Diaz Teodori; María Alejandra; et al. (EDP Sciences, 2026)
Context
Tidal disruption events (TDEs) occur when a star is disrupted by the tidal forces of a supermassive black hole (SMBH), which produces bright multi-wavelength flares. Among these events, AT2020mot has so far exhibited the highest recorded optical polarisation, with tidal shocks proposed as the primary source of its polarised emission.
Aims
We present a comprehensive analysis of 13 TDEs with available polarimetric observations, aiming to determine whether the unusually high polarisation of AT2020mot stems from unique physical processes or arises from mechanisms shared by other TDEs.
Methods
We present new optical polarisation measurements of TDEs obtained from multiple ground-based telescopes, combining them with optical, UV, and X-ray light curves from the Zwicky Transient Facility and the Swift observatory. We derived intrinsic TDE properties – such as SMBH and stellar masses – using MOSFiT and TDEMass, and compared them with those of the sample population.
Results
Our population study reveals that AT2020mot aligns with the broader TDE sample in terms of most physical properties, including blackbody temperature, luminosity, and rise timescales. However, its optical polarisation degree is exceptionally high compared to the low or undetected polarisation observed in other events. Additionally, according to our MOSFiT fit, AT2020mot has an elevated column density, which suggests a more complex environment than is typically assumed.
Conclusions
We conclude that although AT2020mot fits well within the general TDE population in terms of global characteristics, its extraordinarily high polarisation and higher column density challenge current models based purely on shock or reprocessing mechanisms. More extensive, time-resolved polarimetric monitoring of newly discovered TDEs will be critical to determine whether AT2020mot represents an outlier or the extreme end of a continuum of TDE properties.